Tunable graphene-based hybrid plasmonic modulators for subwavelength confinement - Sheng Qu (Nature Portfolio, 2017)
Abstract Electro-optical modulators which work at the near-infrared range are significant for a variety of applications such as communication and sensing. However, currently available approaches result in rather bulky devices which suffer from low integration and can hardly operate at low power consumption levels. Graphene, an emerging advanced material, has been widely utilized due to its tunability by gating which allows one to realize active optical devices. Plasmonic waveguides, one of the most promising candidates for subwavelength optical confinement, provide a way to manipulate light on scales much smaller than the wavelength. In this paper, we combine the advantages of graphene and plasmonic waveguides and propose a tunable graphene-based hybrid plasmonic modulator (GHPM). Considering several parameters of the GHPM, the modulation depth can reach approximately 0.3 dB·μm−1 at low gating voltages. Moreover, we combine GHPM with metal-insulator-metal (MIM) structure to propose another symmetrical GHPM with a modulation depth of 0.6 dB·μm−1. Our modulators which utilize the light-matter interaction tuned by electro-doped graphene are of great potential for many applications in nanophotonics.